2005
DOI: 10.1080/14681810500278436
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful evaluation of sex and relationship education

Abstract: Effective sex and relationship education promotes agency and targets sexual practice as it is socially produced. The aim of evaluation therefore is to contribute to good sexual health through identifying when and how education is promoting agency and changes in sexual practice. Good evaluation takes account of the complexities of the specific object being addressed-sexual practice-which is fluid and essentially social. Innovative study design and the use of rigorous and transparent methods enable evaluators to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Kippax & Stephenson also critiqued the "fetishised" (p.361) commitment to the randomised controlled trial (RCT) as the single gold standard methodology [14]. When charged by the American Psychological Association (APA) with the task of evaluating the state of psychotherapeutic research, Norcross also observed that the EST lists were "oddly person-less" (p.2) and that "most practice guidelines depict disembodied therapists performing procedures on Axis 1 disorders [15].…”
Section: A Historical Perspectivementioning
confidence: 99%
“…Kippax & Stephenson also critiqued the "fetishised" (p.361) commitment to the randomised controlled trial (RCT) as the single gold standard methodology [14]. When charged by the American Psychological Association (APA) with the task of evaluating the state of psychotherapeutic research, Norcross also observed that the EST lists were "oddly person-less" (p.2) and that "most practice guidelines depict disembodied therapists performing procedures on Axis 1 disorders [15].…”
Section: A Historical Perspectivementioning
confidence: 99%
“…According to OFSTED (2002) too few schools engage pupils in planning or evaluating their SRE programmes (p.5) and the monitoring and evaluation of SRE are weak in most cases. Consultation with students on the content and approaches to teaching SRE has long been recognised as vital (Trudell 1993;DfEE, 2000), as is the need for regular evaluation and review involving young people if content is to remain up to date and in line with needs (Kippax & Stephenson, 2005). As a means to illustrate, the next section of the paper turns to data that highlights disjunctions between the content of school sex and relationships education and young people's reported sexual experience, and considers the implications this might have for learning about sex and developing sexual competence.…”
Section: Sexual Competence Government Guidance and Researchmentioning
confidence: 99%
“…This practice of objectivity in relation to sexual practice also served as a basis for contesting the orthodoxy of certain evidentiary practices that have come to dominate the HIV field-in particular the randomized controlled trial, which is sometimes fetishized as the overriding basis for making decisions about HIV prevention programming. In a series of important publications, NCHSR researchers rejected the appropriateness of this method for evaluating sexual health interventions (Kippax & Van de Ven, 1998;Kippax, 2003;Kippax & Stephenson, 2005). Their basic argument was that control trials are unable to account for the complex processes through which social transformation occurs, which are never linear or unidirectional and rarely take place over the short term.…”
Section: The Limits Of Controlmentioning
confidence: 99%
“…In this work, the authors typically counter-pose social interventions to drugs, which are said to be more suitable for randomized evaluation (Kippax 2003;Kippax & Stephenson, 2005). But I wonder if this contrast between the social and the biomedical isn't too easy, especially if we maintain focus on the concept of articulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation